Replication of newly proposed TNM staging system for medullary thyroid carcinoma: a nationwide study. Issue 1 (January 2019) - Mathiesen, Jes Sloth; Kroustrup, Jens Peter; Vestergaard, Peter; Poulsen, Per Løgstrup; Rasmussen, Åse Krogh; Feldt-Rasmussen, Ulla; Schytte, Sten; Londero, Stefano Christian; Pedersen, Henrik Baymler; Hahn, Christoffer Holst; Bentzen, Jens; Möller, Sören; et al.
Abstract : A recent study proposed new TNM groupings for better survival discrimination among stage groups for medullary thyroid carcinoma (MTC) and validated these groupings in a population-based cohort in the United States. However, it is unknown how well the groupings perform in populations outside the United States. Consequently, we conducted the first population-based study aiming to evaluate if the recently proposed TNM groupings provide better survival discrimination than the current American Joint Committee on Cancer (AJCC) TNM staging system (seventh and eighth edition) in a nationwide MTC cohort outside the United States. This retrospective cohort study included 191 patients identified from the nationwide Danish MTC cohort between 1997 and 2014. In multivariate analysis, hazard ratios for overall survival under the current AJCC TNM staging system vs the proposed TNM groupings with stage I as reference were 1.32 (95% CI: 0.38–4.57) vs 3.04 (95% CI: 1.38–6.67) for stage II, 2.06 (95% CI: 0.45–9.39) vs 3.59 (95% CI: 1.61–8.03) for stage III and 5.87 (95% CI: 2.02–17.01) vs 59.26 (20.53–171.02) for stage IV. The newly proposed TNM groupings appear to provide better survival discrimination in the nationwide Danish MTC cohort than the current AJCC TNM staging. Adaption of the proposed TNM groupings by the current AJCC TNM staging system may potentially improve accurateness in survival discrimination. However, before such an adaption further population-based studies securing external validity are needed.